Current Research Status of Climbing Operation Robots for High-Altitude Welding of Steel Structures - Lyu, Hanlin; Wei, Hangxin (Scientific Journal of Technology, 2026)
At present, research on high-altitude welding robots remains relatively limited. In outdoor environments, welding operations in areas such as steel structures and high-rise construction are typically performed manually. This practice poses significant risks to workers’ personal safety. To address this design gap, one promising approach is to integrate climbing robots with welding robots. Accordingly, this paper reviews the current state of development of climbing robots from a design perspective and discusses key design considerations for equipping climbing robots with welding modules.